PREFERENSI DAN FAKTOR PENENTU DALAM PEMILIHAN KERETA CEPAT “WHOOSH” VS TRANSPORTASI JALAN RAYA - Pramesti, Maharani; Budiono; Amelia Hayati (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2026)
The Jakarta–Bandung corridor represents a strategic intercity route with high mobility demand and diverse transport alternatives. The introduction of KCIC Whoosh offers significantly shorter travel time compared to road-based modes; however, it has not automatically shifted user preferences away from shuttle/travel services, intercity buses, and private cars. This indicates that mode choice decisions are influenced not only by travel time, but also by trade-offs involving cost, accessibility, flexibility, and user characteristics. Therefore, this study aims to analyze consumer preferences and identify the key determinants of mode choice between KCIC Whoosh and road transport modes. This study adopts the Discrete Choice Model framework based on the Random Utility Model using a stated preference approach. Data were collected through an online survey targeting respondents with prior travel experience on the Jakarta–Bandung corridor. The analysis applies binary logistic regression under pairwise comparisons between KCIC Whoosh and major road transport modes. The results indicate that KCIC Whoosh is generally preferred by respondents. Speed and safety consistently emerge as the most influential factors in shaping mode choice. However, other attributes remain important depending on the competing mode. Affordability becomes a key barrier in comparison with shuttle/travel services, while accessibility, frequency, comfort, and punctuality significantly influence decisions in comparison with intercity buses. In contrast, income shows a positive association with the choice of Whoosh relative to private cars, whereas accessibility and flexibility remain constraints. Based on survey data collected from 180 respondents using a stated preference approach, these findings highlight that improving the competitiveness of KCIC Whoosh requires not only maintaining its advantages in speed and safety, but also enhancing affordability, strengthening accessibility, and improving service integration to better meet user needs.